WORKING CONDITIONS OF CASUAL WORKERS IN SELECTED CONSTRUCTION FIRMS IN LAGOS STATE, NIGERIA (2015)
The seasonal nature of the construction sector necessitated the use of casual workers (CWs) by construction firms. Critical factors such as size (number of workers and operational branches) and age (year of incorporation) of firm usually affect the working conditions of CWs. Studies of CWs in the sector have not adequately addressed how these factors affect the perception of working conditions, challenges of work and coping strategies adopted. This study, therefore, examined the working conditions of CWs and the intervening roles of size and age of selected construction firms in Lagos, Nigeria. A synthesis of labour market segmentation and rational choice theories provided the conceptual framework. The designs were both survey and exploratory. A two-stage sampling consisting of purposive and simple random techniques were used to select firms and respondents respectively. Three construction firms of different sizes and ages: Julius Berger Nigeria (JBN) (large/oldest), China Civil Engineering Construction Corporation of Nigeria (CCECC) (medium/older) and Plycon Nigeria Limited (PNL) (small/old) were purposively selected. Using Mason’s sample size determination, 1,076 respondents were selected as follows: JBN (679), CCECC (338) and PNL (59). A semi-structured questionnaire was used to elicit information on socio-demographic characteristics, mode of recruitment (direct or indirect), perception about working conditions (wages, job security, safety at work, overtime bonus, relationship with supervisor and medical assistance), challenges of work and coping strategies. Twenty-nine in-depth interviews were conducted with casual workers (18), management staff (9) and officials of Ministry of Labour and Productivity (2) to ascertain the extent of compliance with regulations on recruitment and treatment of CWs. Six case studies were conducted with CWs. Quantitative data were analysed using descriptive and chi-square test statistics at 5% level of significance, while qualitative data were content analysed. Respondents’ age was 40.6±1.0 years, 79.4% were males, 53.6% earned less than N50, 000 monthly and 67.2% had secondary education and above. Respondents from JBN (65.5%), CCECC (69.2%) and PNL (66.1%) were recruited through direct mode of employment. Wages, job security, overtime bonus, relationship with supervisor and medical assistance were jointly perceived by CWs in JBN (52.9%), CCECC (47.0%) and PNL (29.2%) as good. Respondents from JBN (15.8%), CCECC (6.0%) and PNL (12.6%) perceived them as fair, while those from JBN (31.3%), CCECC (47%) and PNL (56.3%) perceived them as poor. Low wage was identified as a common challenge in all the firms. However, other specific challenges in the firms were safety concerns in JBN (56.5%), rigid supervision (58.3%) in CCECC and job insecurity in PNL (57.5%). Frequently adopted coping strategies by CWs were gossiping about management (56.1%) in JBN, mutual aid and support (60.1%) in CCECC and multiple job holdings (57.3%) in PNL. Marital status (x2=261.3), age (x2=410.2), income (x2=431.1) and level of education (x2=184.3) of CWs had positive relationship with perception about working conditions. There was positive association between size and age of firm (x2=138.3), mode of recruitment (x2=285.6), perception of challenges(x2=181.4),coping strategies (x2=186.2) and perception about working conditions (x2 =121).There were disparities in the kind of incentives the firms offered. All the firms did not comply fully with extant regulations and standards in the recruitment and treatment of CWs. Respondents had both pleasant and unpleasant experiences about working conditions and challenges of work in all the firms at one time or another. Size and age of firms affected the working conditions, challenges of work and coping strategies of casual workers in the construction firms in Lagos State. Management of construction firms should continuously improve the working conditions of casual workers in order to mitigate their challenges of work and ensure better coping strategy.